I2MTC 2024 Glasgow - Towards High Resolution Absolute Angle Sensing using Dual-Wavelength Laser Speckle - Gibson, Sam; Charrett, Tom; Tatam, Ralph P. (Cranfield University, 2024)
Data supporting the conference paper 'Towards High Resolution Absolute Angle Sensing using Dual-Wavelength Laser Speckle', presented at the International Instrumentation and Measurement Technology Conference (I2MTC) in Glasgow, in May 2024.
Keywords: dual-wavelength speckle'; 'absolute angle sensing'; 'high resolution tilt sensing'